Sensation seeking and alcohol use: The mediating role of perceived risks and benefits. - González-Iglesias, Beatriz; Gómez-Fraguela, José A.; Gras, María E.; Planes, Montserrat (Anales de Psicología / Annals of Psychology, 2014)
Sensation seeking is one of personality variables more closely linked to the adoption of different risk behaviors, especially the use of alcohol and other drugs. In addition, sensation seeking influences valuation made by individuals about the risks and their possible consequences. The objective of this study is to analyze the relationship between sensation seeking and the consumption of alcohol in a sample of 356 young people aged between 18 and 25 years. In addition, we wanted to explore the possible effect mediator of biased perceptions of individuals about the potential risks and benefits associated with alcohol in the relationship between the personality and alcohol consumption. The results confirm the importance of sensation seeking in the explanation of the consumption of alcohol among young people and the mediating role of perceptions of risks and benefits in the explanation of the relationship. In the discussion of the work discussed their important practical implications when designing specific interventions aimed at preventing the risks associated with the consumption of alcohol in young people.